Recurrence of Postoperative Stress-Induced Cardiomyopathy Resulting from Status Epilepticus - Grant A. Miller; Yousef M. Ahmed; Nicki S. Tarant (Case Reports in Critical Care)
Introduction. Classically, stress-induced cardiomyopathy (SIC), also known as takotsubo cardiomyopathy, displays the pathognomonic feature of reversible left ventricular apical ballooning without coronary artery stenosis following stressful event(s). Temporary reduction in ejection fraction (EF) resolves spontaneously. Variants of SIC exhibiting mid-ventricular regional wall motion abnormalities have been identified. Recent case series present SIC as a finding in association with sudden unexplained death in epilepsy (SUDEP). This case presents a patient who develops recurrence of nonapical cardiomyopathy secondary to status epilepticus. Case Report. Involving a postoperative, postmenopausal woman having two distinct episodes of status epilepticus (SE) preceding two incidents of SIC. Preoperative transthoracic echocardiogram (TTE) confirms the patient’s baseline EF of 60% prior to the second event. Postoperatively, SE occurs, and the initial electrocardiogram exhibits T-wave inversions with subsequent elevation of troponin I. Postoperative TTE shows an EF of 30% with mid-ventricular wall akinesia restoring baseline EF rapidly. Conclusion. This case identifies the need to understand SIC and its diagnostic criteria, especially when cardiac catheterization is neither indicated nor available. Sudden cardiac death should be considered as a possible complication of refractory status epilepticus. The pathophysiology in SUDEP is currently unknown; yet a correlation between SUDEP and SIC is hypothesized to exist.